Special issue with the title “Expanded Visualities: Photography and Emerging Technologies - Stylianou-Lambert, Theopisti; Neocleous, Kleanthis; Fisher, Andrew (My University, 2024)
This editorial introduces the Special Double Issue of Philosophy of Photography (15.1&2), which focuses on the impact of novel technologies on photography and through this on our understanding of the contemporary world. It sketches the contents of the featured articles and articulates some of the technical developments, concerns and questions that inform and link them.
Keywords: photography; emerging technologies